Synthesis of annulated bis-indoles through Au(I)/brønsted acid-catalyzed reactions of (1H-indol-3-yl)(aryl)methanols with 2-(arylethynyl)-1H-indoles - Patil, Nitin T.; Inamdar, Suleman M.; Gonnade, Rajesh Ghanshyam (Organic & Biomolecular Chemistry, 2017)
A general method to access annulated bis-indoles from (1H-indol-3-yl)(aryl)methanols and 2-(arylethynyl)-1H-indoles under the catalysis of the Ph3PAuOTf/Brønsted acid binary catalyst system has been developed. The reaction was found to proceed in a highly efficient manner and benefit from easy-to-make starting materials, broad substrate scope and operational simplicity. The potential of this method has also been exemplified for the synthesis of pyrrole-annulated indoles using 2-(phenylethynyl)-1H-indoles and phenyl(1H-pyrrol-2-yl)methanols. Furthermore, the use of a ternary catalyst system, involving PdCl2/Brønsted acid/Ph3PAuOTf catalysts, has been realized for the synthesis of annulated bis-indoles starting directly from 2-(phenylbuta-1,3-diyn-1-yl)aniline and (1H-indol-3-yl)(aryl)methanol. Mechanistically, this reaction is very interesting since the overall process involves three different catalytic cycles catalyzed by three different catalysts in a relay fashion.